A taxonomic description of the leafhopper fauna (Homoptera : Cicadellidae) in association with Restionaceae - Davies, David Mabon (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1986.